American physician Samuel A. Levine and his contribution into the cardiac rehabilitation - David M. Aronov (Concilium Medicum, 2021)
The greatest contribution to the formation of the modern concept of early, from the first days of acute myocardial infarction (MI), activation of patients and a decisive rejection of the conservative tactics of long-term immobilization was made in 1952 by the American cardiologist Samuel Albert Levine, who recommended the treatment of patients in a chair. In one of his articles, he called the allegedly protective myocardial effect of strict bed rest for cardiac patients a myth [1].